Linkages between CRM technologies, knowledge applications and first call resolution in inbound call centres - Abdullateef, Aliyu Olayemi; Mohd Mokhtar, Sany Sanuri; Yusoff, Rushami Zien (Inderscience Publishers, 2013)
This empirical research aim at establishing the relationship between CRM technologies, knowledge management and first call resolution within the inbound call centres. The results indicate that CRM organisation and technology–based CRM are major antecedents of call centre knowledge management.The research finding also shows that the strength of conflict resolution in call centres strongly depend on proper knowledge management skills.It practically availed managers inherent opportunities in call centre agent's ability to understand the impact of using CRM technologies and knowledge applications in adding value to job performance and meeting customers' requirements. Alternative recommendations are suggested for future researchers.